A comparative study between brasilian and portuguese reality about urban solid waste management - Gonçalves, Marcelino de Andrade; Queirós, Margarida Maria Araújo; Gonçalves, Alexandre Honig (Sociedade & Natureza, 2016)
This research aimed to analyze and critically confront the situation of the management of municipal solid waste in Brazil and Portugal. Rational research methods were used: a case study and a comparison. The results show that Brazil still suffers from organizational, systems and methods for proper management of solid waste, while Portugal has an organized managerial system, nevertheless menaced by the financial crisis. The specific characteristics and the context are clearly disparate across countries, however, what draws attention is the effectiveness of difference in the application of the proposed management models by the States themselves.